(untitled) (Sains Humanika, 2013)
The great demand for business communication skills among graduates has urged universities to develop Englishbusiness communication courses, which lie under the domain of â€˜English for Specific Purposesâ€™. This paper aims to conduct a ’needs analysis’ of Writing for Professional Purposes course students at the School of Humanities, Universiti Sains Malaysia (USM). It is part of a study which aims at gathering pertinent information from multiple sources including students, graduates of the Writing for Professional Purposes course, employers, and an ESP teacher. Hutchinson and Watersâ€™ model of needs analysis used in the present study to explorethe perceptions of graduates of the courseon the course studentsâ€™ target needs with regards to written business communication skills. The results demonstrate that a few written business communication skills such as writing emails, resumes and reportsare highly important in todayâ€™s workplace. Thus it is vital for students of Writing for Professional Purposes course to be prepared with the needed written business communication skills. The study indicates that generally the course is in line with the studentsâ€™ target needs.